Haarzuilens. Dorp uit de schaduw van het kasteel (Bulletin KNOB, 1996)
The history of the village of Haarzuilens is unique for The Netherlands. The relocation of the village is an inseparable part of the new infrastructure around the castle, being the result of a compromise between the wishes of the baron, who had larger private grounds in mind, and the wishes of the public authorities allowing the relocation, provided that there would be the advantage of shorter routing.The compromise consists of a village with a characteristic road system, which - partly due to economizing - gave the various roads their present status. The project was related to a draft plan by Cuypers, in which an extension on the east side of the village had been planned, but it was worked out by Jos Cuypers in accordance with the ideas of notably Henri Copijn. A first symmetrical design was not executed, since it met with problems concerning the purchase of the grounds.Another important fact is that the defensible character which Haarzuilens was meant to have, was eventually only expressed in the construction of walls and a moat. Looking at the old village one discovers that the earlier Haarzuilens had no defensive character at all. Haarzuilens was relocated, but actually this was restricted to the name, not the architecture, of the village. The village square and the functions of the buildings, such as the pub-townhall, are the most direct references to the old village of Haarzuilens. We may state that this was a new creation, reflecting great vision, unusual for the Netherlands.The medieval character which was deliberately aimed at, is clearly noticeable in the first designs of the townhall. This is the only building with two building layers, thus emphasizing its status. It was executed in a much more austere style. The unusual colour combination of the paintwork in the village is striking, stressing the relation to the Van Zuylen family. On the recommendation of Jos Cuypers a few young colleagues were appointed for the construction of the other buildings. Steward Frans Luyten played a major part in this. He can be regarded as the pivot of the restoration, since he was on friendly terms with the baron, the architects and others. The huge amount of correspondence is also a sign of a far-reaching influence on transactions, appointments and designs.The matter of Springer is a chapter in itself and continues to raise a number of questions. At any rate his design is clearly different from the other designs. One wonders whether Springer was pushed out because of his father's conflict with Cuypers, his views on design or his character. Copijn, on the other hand, appeared to get on well with Cuypers, Luyten and the baron. The ideas of Cuypers and Luyten were incorporated in Copijn's designs. The fact that the complex as a whole is unique and still in an almost unblemished state, makes Haarzuilens an unparalleled cultural phenomenon, justifying national protection.